Remoteness, farm production, and dietary diversity in Nepal - Singh, Tushar; Kishore, Avinash; Alvi, Muzna (International Association of Agricultural Economists, 2024)
This paper explores the relationship between agriculture, dietary diversity, and market access in Nepal, testing the complex causal chains involved, and the nuanced connections between production diversity and dietary diversity among smallholder farmers. While diversifying farm production could enhance dietary diversity, the case of Nepal indicates a varied and context specific relationship. Market access emerges as a crucial factor, often exerting a more significant impact on smallholder farm households than production diversity. Access to markets not only influences economic viability but also contributes directly to food and nutrition security, offering a practical solution to address dietary needs. Focusing on Nepal's diverse terrain, the study analyzes the interplay of remoteness, market access, irrigation availability, and complementary inputs in shaping farmers' decisions, providing valuable insights into sustainable agricultural strategies for improved dietary outcomes in low- and middle-income countries.